RELATIONSHIP BETWEEN SERUM PROGESTERONE AND ESTRADIOL-17β AND EMBRYONIC LOSS IN FRISIAN COWS UNDER EGYPTIAN CONDITION - ABU EL-HAMD, M A; KADOOM, A K; M FOUAD, W F; HASSOUNA, S H (The Indian Journal of Animal Reproduction, 2022)
Association between circulating progesterone and oestradiol-17β concentrations and embryonic loss in Frisian cows (n=105) under Egyptian condition was investigated. Total embryonic losses in present study were 26.4%. On d25, progesterone (P4) concentrations and sonography revealed 79.3% cows were continuing gestation and 20.7% lost their pregnancies (early embryonic loss, EEL). Furthermore, 7.4% cows with late embryonic loss (LEL) were detected between d25-42. An increase in P4 levels started from day 4 to 7 in cows diagnosed pregnant compared to low P4 in cows that lost pregnancy (p<0.05). Cows with LEL had decrease in P4 from d28. Estradiol (E2) concentrations increased (p<0.05) in cows with EEL starting from d4 to 21 after AI compared to cows diagnosed pregnant. Starting from d4 to 40 after AI, P4/E2 ratio was higher (p<0.05) in cows diagnosed pregnant compared to cows exhibiting EEL loss, while cows with LEL had highest P4/E2 ratio till d25 post-AI and declined from d28 to 40.